Using fairy tales to improve students writing skills: a case study - Obeid, Olga El Hage (Beirut University of Balamand. Faculty of Arts and Social Sciences, 2013)
The aim of this research study is to examine how fairy tales can be used in an ESL classroom in order to improve learners writing skills and vocabulary capacity. It also investigates the students and teacher s perceptions and attitude towards integrating fairy tales in the ESL classroom. A total of twelve third grade students of the target school completed a questionnaire which aimed at clarifying their opinion about fairy tales in general and their usage in their English class. Observations and diary entries were written and analyzed after each session. A pre-test, a pre-questionnaire, a post-test, and a post-questionnaire were used as a control to track the progress of the students and their attitude from the beginning of the study until the end. A writing checklist was used to analyze the content of the students written samples. The results obtained from the analysis of the written samples, the pre-test and post-test, were positive and every student progressed in various areas. Students enjoyed using fairy tales in their English class and even favored them over their assigned story book. Fairy tales and their accompanying activities were able to help learners improve their writing skills and use rich vocabulary while writing. The varied activities met each of the learners multiple learning styles and developed a more positive approach to the idea of writing. The study showed that fairy tales can improve the skill of writing and vocabulary knowledge. If used appropriately, fairy tales can promote a positive classroom atmosphere.
: Mémoire
Keywords: English Language Education; L enseignement de la Langue Anglaise